Model aplikasi desktop multi language menggunakan Netbeans Platform - Rano Kurniawan; Henderi Henderi (Progresif: Jurnal Ilmiah Komputer, 2021)
AbstractMany researches on desktop-based applications have been carried out, but no one has developed and discussed specific multi-language desktop applications. This paper aims to develop a multi-language desktop application using the Netbeans Platform. Multi-language desktop applications are developed with an Agile approach that focuses on rapid development. Application development is carried out through the stages of requirements, design, develop, testing, and evaluation. Identification of application requirements is carried out on functional and non-functional requirements. The design stage is carried out using a unified modeling language approach, deploying using the Java programming language and Netbeans platform, testing with a black box approach, and evaluation is carried out through focus group decisions (FGD). FGDs were conducted by involving application owners, application developers, desktop application experts, application industry players, and end users. The evaluation results show that the developed multi-language-based desktop application has an assessment score of 83.7 with a very good predicate. The application of the resulting multi-language-based desktop application has implications for increasing user interest in using the application.Keywords: desktop application, multi language, Netbeans Platform AbstrakPenelitian tentang aplikasi berbasis desktop telah banyak dilakukan, namun belum ada yang mengembangan dan membahas tentang aplikasi desktop multi language secara spesifik. Paper ini bertujuan mengembangkan aplikasi desktop multi language menggunakan Netbeans Platform. Aplikasi desktop multi language dikembangkan dengan pendekatan Agile yang fokus pada perkembangan yang cepat. Pengembangan aplikasi dilakukan melalui tahapan requirements, design, develop, testing, dan evaluation. Identifikasi kebutuhan aplikasi dilakukan terhadap fungsional dan non functional requirements. Tahapan desain dilakukan dengan pendekatan unified modeling language, deploy menggunakan bahasa pemrograman java dan Netbeans platform, testing dengan pendekatan black box, dan evaluasi dilakukan melalui focus group decision (FGD). FGD dilakukan dengan melibatkan pemilik aplikasi, pengembang aplikasi, ahli aplikasi desktop, pelaku industri aplikasi, dan end user. Hasil evaluasi menunjukan bahwa aplikasi desktop berbasis multi language yang dikembangkan memiliki skor penilaian sebesar 83,7 dengan predikat sangat baik. Penerapan aplikasi desktop berbasis multi language yang dihasilkan berimplikasi kepada peningkatan minat user dalam menggunakan aplikasi.Kata kunci: aplikasi desktop, multi language, Netbeans Platform